2018
DOI: 10.1051/matecconf/201819201020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-vinylpyrrolidone/Acrylic acid nanoparticles for drug delivery: Method optimization

Abstract: There are various approaches to deliver therapeutic agents to the preferred target. Polymeric nanoparticles were found to have pleasing suitability as a drug carrier. The goal of this research was to optimize the synthesis method to obtain the desirable %yield and particle properties of the new biocompatible polymer-based nanoparticles. The non-toxic polymer, N-vinyl pyrrolidone (NVP) and a widely used hydrophilic biocompatible acrylic acid (AA) monomer were used to form the drug nanocarriers. The synthesis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…PVPAA copolymer was synthesized by a polymerization reaction between NVP and AA at a monomer molar ratio of 1:3. A previous study found that the % yield of this ratio was almost twice as great as that obtained at a monomer ratio of 1:1 [12]. The synthesis scheme is presented in Figure 1.…”
Section: Synthesis Of Pvpaamentioning
confidence: 86%
See 2 more Smart Citations
“…PVPAA copolymer was synthesized by a polymerization reaction between NVP and AA at a monomer molar ratio of 1:3. A previous study found that the % yield of this ratio was almost twice as great as that obtained at a monomer ratio of 1:1 [12]. The synthesis scheme is presented in Figure 1.…”
Section: Synthesis Of Pvpaamentioning
confidence: 86%
“…PVPAA was synthesized using a surfactant-free emulsion polymerization reaction between NVP and AA. The synthesis was modified from a previously reported procedure [12]. Briefly, 0.05-0.2%wt V50 (the initiator) was dissolved in 50 mL of deionized water heated at around 70 • C. The mixture was purged with nitrogen gas to create an inert environment.…”
Section: Synthesis Of Pvpaamentioning
confidence: 99%
See 1 more Smart Citation
“…The PNPs were synthesized in accordance with our previous study using acrylic acid (AA) and 1-vinyl-2-pyrrolidone (VP) as monomers for the synthesis reaction. 24 Then, the PNPs were conjugated with thiol groups and preactivated with 2MNA. VP is a hydrophilic monomer and commonly acquired as a PNP stabilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Th eir high surface-to-volume ratio enables improved interactions with the environment, making them promising for wound care, drug delivery and biotechnology applications. Nanofi bres can thus be used for biomedical applications such as tissue engineering, wound healing processes and targeted drug delivery systems [3][4][5][6][7][8][9]. According to the results of several research groups, nanofi brous mats have the ability to absorb large concentrations of wound exudates without causing infections, and release anti-microbial and anti-infl ammatory agents.…”
Section: Introductionmentioning
confidence: 99%